PROBLEMS AND PRIORITY AREAS FOR THE DEVELOPMENT OF ECONOMIC RELATIONS BETWEEN UKRAINE AND CHINA - BONDARENKO, Valerii; LI, Zehao (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Trade cooperation between Ukraine and China is based on positive historical experience. The institutional, including legislative, regulatory, and legal framework for Ukraine-China trade relations covers political, defense, trade and economic, cultural, educational, scientific and technical, tourism, migration, investment, and transport and logistics components. Trade relations have been the most developed so far. During 2001-2020, there was a stable trend towards an increase in foreign trade turnover. At the same time, for Ukraine, the commodity structure of trade with China is characterized by negative indicators, both in quantitative (negative trade balance in goods) and qualitative (predominance of raw material exports, low level of commodity diversification, dominance of high-tech goods in imports) dimensions. The development of Ukrainian-Chinese cooperation is becoming more multidirectional. Both sides approach the establishment of more productive interaction primarily from the standpoint of ensuring national interests. The PRC takes into account Ukraine’s real capabilities and prospects in the agricultural sector and developments in technical fields, such as aircraft construction, for example. For Ukraine, China is currently a market for promoting its products and a source of investment in the economy. The attractiveness of this direction of Ukraine’s foreign policy is determined by many factors, not the least of which is the ever-growing political and economic weight of China in the world. The study has identified the following factors that contribute to the growing interest of Chinese investors in Ukrainian markets: openness and economic freedom, increased market potential, successful investments in the past; signing of the Association Agreement with the EU and further strengthening of European integration processes in Ukraine. For Ukraine, cooperation with China opens up new opportunities for international trade and economic development, as China is one of the most influential countries with high economic, scientific and technological development. Thus, the food market in China is not only one of the largest in the world, but is also characterized by the world’s fastest growth rates and complex structure. A deep understanding of the detailed features of individual product segments and the Chinese food market as a whole is a key factor in unlocking its potential for Ukraine.